Waktu Dan Suhu Optimum Dalam Produksi Asam Oksalat (H2c2o4) Dari Limbah HVS Dengan Metode Peleburan Alkali - Nurul, Nurul; Chadijah, St.; Ramadani, Kurnia (Al-Kimia, 2017)
Waste paper HVS can be used as raw material for the manufacture of oxalic acid containing 63 % cellulose. This study aims to determine the optimum time and temperature in the production of oxalic acid from waste paper with alkali fusion method. Oxalic acid can be made using an alkaline solution ( NaOH 40 % ) with multiple stages such as hydrolysis, filtration, precipitation with CaCl2, acidification with H2SO4 and efflorescence. The time variation used are 60, 70, 80 and 90 minutes. While the temperature variation used is 75oC, 90oC, 105oC and 120oC. From the research that has been done by using waste paper as much as 15 grams of HVS, the optimum time is on the 70th minute and the fusing temperature obtained by the temperature of 105oC. Weight of oxalic acid crystals obtained an average of 1.8043 g and yield of oxalic acid after permanganate test is obtained by 6.8537 %.